2001
DOI: 10.1038/sj.leu.2401982
|View full text |Cite
|
Sign up to set email alerts
|

HLA class I antigen cell surface expression is preserved on acute myeloid leukemia blasts at diagnosis and at relapse

Abstract: Human leukocyte antigens (HLA) class I molecules restrict the interaction between cytotoxic T cells and target cells. Abnormalities in HLA class I antigen expression and/or function may provide tumor cells with a mechanism for escaping immune surveillance and resisting T cell-based immunotherapies. The potential for applying T cell-based immunotherapy in the treatment of acute myeloid leukemia (AML) has stimulated interest in analyzing HLA class I antigen expression on leukemic blasts in this disease. Little i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 18 publications
2
32
1
Order By: Relevance
“…In these cases, the selective pressure on APM components could be because of induction and consolidation chemotherapy. Studies by Wetzler et al 20 showed that general MHC class I downregulation on AML blasts could not be detected in patients from ID to relapse, confirming our data on persistent high expression of MHC class I HC from ID to relapse in all four patients evaluated ( Figure 5b). However, from our studies presented here, we conclude that the pattern of peptides presented on the MHC class I of AML blasts can change in disease progression and can, therefore, promote escape from the immune system.…”
Section: Apm Expression In Aml Progressionsupporting
confidence: 91%
See 2 more Smart Citations
“…In these cases, the selective pressure on APM components could be because of induction and consolidation chemotherapy. Studies by Wetzler et al 20 showed that general MHC class I downregulation on AML blasts could not be detected in patients from ID to relapse, confirming our data on persistent high expression of MHC class I HC from ID to relapse in all four patients evaluated ( Figure 5b). However, from our studies presented here, we conclude that the pattern of peptides presented on the MHC class I of AML blasts can change in disease progression and can, therefore, promote escape from the immune system.…”
Section: Apm Expression In Aml Progressionsupporting
confidence: 91%
“…These antibodies have been used in previous studies of APM component expression in various tissues, 19,20 and were kindly provided by Dr S Ferrone (Roswell Park Memorial Institute, Buffalo, NY, USA). Staining for the different APM components was performed using standard immunohistochemical staining procedures with heat-induced antigen retrieval, and visualization of staining was performed using the avidin-biotin peroxidase method with diaminobenzidine chromatogen (LMP2, LMP7, MHC class I HC) or En-Vision (TAP1, TAP2, b2m; DakoCytomation, Glostrup, Denmark).…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated that HLA Class I antigen expression is preserved on the surface of AML blasts. 58 HLA Class I molecules bind antigenic peptides and present them to cytotoxic (CD8+) T cells. The recognition of these peptides by cytotoxic T cells triggers a series of events that may result in lysis of target cells.…”
Section: Discussionmentioning
confidence: 99%
“…In a study on 25 acute myeloid leukemia (AML) patients at diagnosis, HLA class I expression was found to be preserved in all cases. 3 The potential of adoptive T-cell immunotherapy by donorlymphocyte infusions for treating leukemic patients has stimulated interest in HLA class I expression on leukemic cells that could impact on the efficacy of donor-lymphocyte infusions. An HLA and microsatellite genotyping analysis of 44 samples of freshly isolated leukemic blasts did not reveal any case of haplotype loss, although a downregulation of HLA class I expression was observed in 9.1% of the patients samples.…”
Section: Introductionmentioning
confidence: 99%